ATYPICAL FORMS OF STRABISMUS AND THEIR TREATMENT - Savrinisa Nazirdzhanovna Ibragimova (Modern American Journals, 2025)
Atypical forms of strabismus, including Brown syndrome and Duane syndrome, are complex and varied oculomotor disorders that require a careful diagnostic approach and individualized treatment. This article presents current data on the etiology, clinical presentation, diagnostic methods, and modern treatment options for these conditions. Brown syndrome is characterized by restricted elevation of the eye during adduction, due to mechanical difficulty of the superior oblique tendon passing through the trochlea. This is confirmed by limitations of elevation in adduction, a V-pattern deviation, and positive traction test results, supported by MRI/CT findings. Treatment may be conservative (observation, steroid injections in inflammatory forms) or surgical (tenotomy, tenectomy, silicone expander implantation). In contrast, Duane syndrome is a congenital dysinnervation disorder featuring limited horizontal eye movements, globe retraction, and often caused by aplasia or hypoplasia of the abducens nerve (cranial nerve VI), with compensatory innervation of the lateral rectus by the oculomotor nerve (cranial nerve III). Diagnosis is clinical, with MRI or genetic testing used as needed. Therapy includes correction of refractive errors, amblyopia treatment, use of prisms, and, in cases of significant cosmetic or functional impairment, surgical intervention such as muscle relaxation, transposition surgery, Y-splitting, and more. Both conditions are characterized by a wide range of manifestations and the absence of a universal surgical algorithm. Therefore, treatment strategy must be based on thorough clinical analysis and patient-specific considerations.
Keywords: Brown syndrome, Duane syndrome, incomitant strabismus, tenotomy, tenectomy, dysinnervation.